Tradisi Pokat Kahangi dalam Membentuk Karakter Kerjasama Masyarakat - Rohman Rohman; Rika Fitri; Rika Sartika (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
The pokat kahanggi tradition, a cultural practice in Mandailing society, is crucial in shaping cooperation, social solidarity, and community cohesion. This research examines the practice of this tradition in the Huta Padang Village community and its impact on these values. Data was collected through in-depth interviews with traditional leaders, community leaders, and residents involved in the practice, as well as participatory observation of related activities. The Miles and Huberman interactive model was used for data analysis. The results indicate that pokat kahanggi remains an integral part of the Huta Padang community's social life, acting as an integrative mechanism that strengthens relationships between kahanggi members through consensus in various aspects of life. It also serves as an informal education tool, instilling values of mutual cooperation, responsibility, and togetherness to the younger generation. This tradition aligns with concepts of moral knowing, moral feeling, and moral action, instilling social ethical values and virtues. To preserve and adapt pokat kahanggi, efforts are needed to face modernization challenges. This study contributes to understanding how local traditions can serve as an effective character education instrument.